Different Influence of Gas Accretion on the Evolution of Star-forming and Non-star-forming Galaxies - Min Bao; Wenlong Zhao; Qirong Yuan (The Astrophysical Journal, 2024)
Using integral field spectroscopic data from the Mapping Nearby Galaxies at Apache Point Observatory survey, we investigate the spatially resolved properties and empirical relations of a star-forming galaxy and a non-star-forming galaxy hosting counterrotating stellar disks (CRDs). The DESI g , r , z color images reveal no evidence of merger remnants in either galaxy, suggesting that gas accretion fuels the formation of CRDs. Based on the visible counterrotation in the stellar velocity field, we can fit a spatial boundary to distinguish the inner and outer regions dominated by two stellar disks in each galaxy. In the inner region of the star-forming CRDs, stars are corotating with ionized gas, and the stellar population is younger. Comparison of the star-forming main-sequence relations between the inner and outer regions reveals enhanced star formation in the inner region. Given the abundant preexisting gas in the star-forming galaxy, collisions between preexisting and external gas efficiently consume angular momentum, triggering star formation in the inner region. Conversely, in the outer region of the non-star-forming CRDs, stars are corotating with ionized gas, and the stellar population is younger. Comparison of the stellar mass–metallicity relations between the inner and outer regions indicates enriched gas-phase metallicity in the outer region. Considering the less abundant preexisting gas in the non-star-forming galaxy, external gas could preserve angular momentum, fueling star formation in the outer region. Overall, gas accretion exhibits different influences on the evolution of star-forming and non-star-forming galaxies.